Assessment of indoor air quality in geriatric environments of southwestern Europe - Pereira, Ermelinda (2018)
The objective of this study was to evaluate physical–chemical and microbial indicators of indoor air quality in three nursing houses (NHs) located in rural areas of the northeast of Portugal. The parameters were measured during two campaigns (winter and summer), twice a day, and in four distinct spaces for spatial variability assessment: dining room, living room, double bedroom and outdoor of the NHs. Physical–chemical indicators were assessed by using a Graywolf IQ 610 probe. Airborne microbial levels were evaluated by direct impaction to the culture media, and subsequently, the microorganisms were identified molecularly. Mean concentrations of physical–chemical (with the exception of total volatile organic compounds, TVOCs) and microbial indicators did not exceed the legal limits. Overall, in all NHs, the indoor-to-outdoor (I/O) concentration ratios of chemical and biological pollutants were ≤ 1 in the summer, while in the winter were > 1. Bacillus, Micrococcus and Staphylococcus were the dominant bacterial genera, and Aspergillus, Cladosporium and Penicillium were the dominant fungal genera. The diversity of species was higher in summer. The main results suggest that a good air quality prevails in all studied spaces, although conditions less desirable have been identified in winter, indicating the need to deepen the study of air quality in these places, since these are occupied by elderly people who are more susceptible to infections.